Analisis Saluran Pemasaran Ayam Buras di Kabupaten Banyuwangi - Anang Febri Prasetyo; Bayu Aminulloh Fatah (Politeknik Negeri Jember, 2019)
The aim of the study was to determine the forms of marketing channels for local chickens, find out the size of the margins and the benefits of each party involved in the marketing of local chickens, find out the level of efficiency in each form of local chicken marketing channels in Banyuwangi regency. The number of respondents is as many as 195 respondents consisting of breeders, collectors, wholesalers, Chicken Slaughterhouses, retailers and consumers. The method used is descriptive analysis method and mathematical analysis. The results showed that there were 4 forms of marketing channels for local chickens in Banyuwangi Regency. Channel 1 (breeders to consumers), channel 2 (breeders, collectors and consumers), channel 3 (breeders, collectors, wholesalers and consumers), channel 4 (breeders, collectors, wholesalers, Chicken Slaughterhouses, retailers and consumers). The largest total marketing margin was in channel 4, which was Rp51,000.00 and the smallest total margin was in channel 1 of Rp0,00. The highest number of profits in the marketing of local chickens in Banyuwangi Regency was in channel 4 Chicken Slaughterhouse of Rp15,433.33 per chicken and the smallest profit in channel 2 traders is Rp5,893.37 per chicken, for the largest percentage of profit from the marketing of local chickens in the Regency Banyuwangi is in channel 4 Chicken Slaughterhouse at 31% and for the smallest percentage of profit is channel 1 farmer by 5%. The level of marketing efficiency of native chickens in Banyuwangi Regency based on marketing costs and marketing margins is declared efficient.